Noninvasive diffusion tensor imaging of evolving white matter pathology in a mouse model of acute spinal cord injury - Kim, Joong Hee; Loy, David N.; Liang, Hsiao-Fang; Trinkaus, Kathryn; Schmidt, Robert E.; Song, Sheng-Kwei (Magnetic resonance in medicine, 2007)
We examined in vivo measurements of directional diffusivity derived from diffusion tensor imaging (DTI) to study the evolution of ventrolateral white matter (VWM) changes following contusive spinal cord injury (SCI) in C57BL/6 mice at 1, 3, 7, and 14 days postinjury. Relative anisotropy maps provided excellent gray matter (GM)/white matter (WM) contrast for characterization of evolving WM injury at all time points. Longitudinal DTI measurements clearly demonstrated rostral‐caudal injury asymmetry. Axial diffusivity provided a sensitive, noninvasive measure of axonal integrity within the injury epicenter and at remote levels. Quantitative measurements of axial and radial diffusivities in VWM showed a trend of acute primary axonal injury followed by delayed, subacute myelin damage at the impact site, with good histological correlation. Magn Reson Med 58:253–260, 2007. © 2007 Wiley‐Liss, Inc.